Effect of remdesivir on mortality rate, need of intubation and mechanical ventilation in COVID-19 positive patients: a retrospective observational study - Nikalje, Anand; Tripathy, Srabani; Talekar, Rahul S.; Mane , Sumedh B. (International Journal of Research in Medical Sciences, 2023)
Background: The symptoms of SARS-CoV-2 infection vary widely, from asymptomatic disease to pneumonia and life-threatening complications, including acute respiratory distress syndrome, multisystem organ failure, and ultimately, death. Remdesivir has broad spectrum of activity against members of several virus families, including filoviruses and coronaviruses. Remdesivir is a potent inhibitor of SARS-CoV-2 replication in human nasal and bronchial cells. Methods: This is a prospective and observational study conducted in patients of either gender, age more than 18 years with confirmed diagnosis of COVID-19 by RT-PCR. A predesigned, pretested and semi structured questionnaire containing socio demographic details like age, sex, BMI, comorbidities, findings of systemic examination of the cases, dose and duration of Remdesivir received and adverse effect due to therapy was used to collect the data. Results: Mean age of the patients were 56.19±10.93 years. Male patients were 66% and 34% patients were female. After receiving the remdesivir, 43% of the patients needed bag mask and 27% of the patients maintained on room air oxygen. Non-invasive ventilation required in 19% of the patients and 11% of the patient required mechanical ventilation. s14% of the patients needed admission in the ICU. 3.5% of the patients were died and 96.5% patients were discharged from the hospital. Conclusions: Remdesivir reduces the need of non-invasive oxygenation and mechanical ventilation. Mortality was seen in 3.5% patients, henceforth remdesivir, is an effective drug for moderate to severe COVID-19, if given in early stages of infection.